2020
DOI: 10.1111/ans.16272
|View full text |Cite
|
Sign up to set email alerts
|

Pancreatic cancer in the Australian population: identifying opportunities for intervention

Abstract: Pancreatic cancer is a disease associated with a poor overall survival. Advances in surgical techniques have helped improve outcomes of patients who are amenable to surgical resection. Sadly, surgery is amenable in only a small percentage of patients with the disease. Thus, there is a need to direct efforts at reducing the overall risk of pancreatic cancer or facilitating its early detection. The current review focused on collating all the literature published to date on pancreatic cancer in Australia with an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 74 publications
0
4
0
Order By: Relevance
“…Kidney and pancreatic cancer and multiple myeloma incidence was found to be higher in younger cohorts but other local evidence showed that overall incidence may be stabilising 41 or moderately increasing, 25 , 42 respectively. The incidence of uterine cancer increased in younger cohorts, but this was not seen for ovarian cancer.…”
Section: Discussionmentioning
confidence: 87%
“…Kidney and pancreatic cancer and multiple myeloma incidence was found to be higher in younger cohorts but other local evidence showed that overall incidence may be stabilising 41 or moderately increasing, 25 , 42 respectively. The incidence of uterine cancer increased in younger cohorts, but this was not seen for ovarian cancer.…”
Section: Discussionmentioning
confidence: 87%
“…Considering that the 5‐year survival rates (2011–2015) for PDAC are among the lowest of all cancers in Australia (9.1% for men and 9.2% for women 42 ), we need to focus on improving delivery and accessibility to pancreatic cancer care in the years to come. A recent review by the authors 43 has highlighted numerous opportunities for intervention. Among others, the creation of environments that are supportive for healthy behaviour choices for all Australians, focusing on reduction in smoking and improvements in diet (including considering legislations to help these endeavours) and promoting the benefits of weight loss in overweight and obese persons, increasing national funding for PDAC research 43 (to facilitate a better understanding of tumour biology 44 and early detection of the cancer 45 ), and addressing the issue of accessibility to care (increasing utilization of surgery 46 and chemotherapy 47 ), as well as bridging the urban–rural chasm 48 …”
Section: Discussionmentioning
confidence: 99%
“…A recent review by the authors 43 has highlighted numerous opportunities for intervention. Among others, the creation of environments that are supportive for healthy behaviour choices for all Australians, focusing on reduction in smoking and improvements in diet (including considering legislations to help these endeavours) and promoting the benefits of weight loss in overweight and obese persons, increasing national funding for PDAC research 43 (to facilitate a better understanding of tumour biology 44 and early detection of the cancer 45 ), and addressing the issue of accessibility to care (increasing utilization of surgery 46 and chemotherapy 47 ), as well as bridging the urban-rural chasm. 48 Another aim of the present study was to investigate if there is a difference in survival between PDAC involving the head and uncinate process of the pancreas versus the body and tail.…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of pancreatic cancer is increasing globally with 5 year survival rates amongst the lowest of all cancers. 1 The majority of patients are not suitable for curative intent treatment at presentation; either due to a primary that is locally unresectable, metastatic disease or poor performance status. For patients with lesions in or near the head of the pancreas only 15-20% are suitable to undergo curative intent treatment in the form of pancreaticoduodenectomy or 'Whipples' procedure at the time of diagnosis.…”
Section: Introductionmentioning
confidence: 99%